2002
DOI: 10.1016/s0040-1951(01)00207-4
|View full text |Cite
|
Sign up to set email alerts
|

Geodynamic significance of the Raspas Metamorphic Complex (SW Ecuador): geochemical and isotopic constraints

Abstract: The Raspas Metamorphic Complex of southwestern Ecuador is regarded as the southernmost remnant of oceanic and continental terranes accreted in the latest Jurassic -Early Cretaceous. It consists of variably metamorphosed rock types. (1) Mafic and ultramafic rocks metamorphosed under high-pressure (HP) conditions (eclogite facies) show oceanic plateau affinities with flat REE chondrite-normalized patterns, eNd 150 Ma ranging from + 4.6 to 9.8 and initial Pb isotopic ratios intermediate between MORB and OIB. (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 52 publications
1
20
0
1
Order By: Relevance
“…Given the large natural variations in Sr-Nd isotope compositions and in Sr and Nd concentrations of subducting sediments and the fact that solid-fluid partition coefficient for sediment for Sr and Nd are close to 1 at appropriate temperatures of 650° and 700°C (Johnson and Plank, 1999), bulk mixing can be used as a simplifying model for comparative purposes. Admixing of a metasedimentary component as sampled in the Raspas complex (Bosch et al, 2002; this study) to a MORB-type eclogite produces mixing trajectories that come close to the composition of the zoisite vein and the zoisite eclogites. Terrigenous sediments, represented by sediments from the Lesser Antilles arc, possess the appropriate Sr-Nd isotope characteristics to produce zoisite eclogite compositions in Sr-Nd isotope space by mixing.…”
Section: Constraints On Fluid Sourcesmentioning
confidence: 82%
See 2 more Smart Citations
“…Given the large natural variations in Sr-Nd isotope compositions and in Sr and Nd concentrations of subducting sediments and the fact that solid-fluid partition coefficient for sediment for Sr and Nd are close to 1 at appropriate temperatures of 650° and 700°C (Johnson and Plank, 1999), bulk mixing can be used as a simplifying model for comparative purposes. Admixing of a metasedimentary component as sampled in the Raspas complex (Bosch et al, 2002; this study) to a MORB-type eclogite produces mixing trajectories that come close to the composition of the zoisite vein and the zoisite eclogites. Terrigenous sediments, represented by sediments from the Lesser Antilles arc, possess the appropriate Sr-Nd isotope characteristics to produce zoisite eclogite compositions in Sr-Nd isotope space by mixing.…”
Section: Constraints On Fluid Sourcesmentioning
confidence: 82%
“…They have trace element characteristics suggesting an affinity to seamounts . The metasedimentary rocks are graphite-bearing garnet mica-schists interpreted as dominantly terrigenous sediments deposited at the Andean continental margin and incorporated into an accretionary prism (Bosch et al, 2002), but less silicic, metavolcanic schists also occur. The peridotites from the El Toro formation are serpentinized to variable degrees (≤ 10 to 95%).…”
Section: Associated Blueschists Metasedimentary Rocks and Peridotitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Strike-slip displacement of these terranes from southern Mexico may play a role in their exhumation prior to emplacement against the Yucatán Block later in the Cretaceous. The Raspas blueschist of southern Ecuador (Arculus et al 1999;Bosch et al 2002) may also originate at a west-facing trench.…”
Section: Plate Reconstructions and Reference Framesmentioning
confidence: 99%
“…In contrast to this finding, Aspden et al (1992) reported a geotectonic event in the Late Cretaceous (65-85 Ma) as the latest datable event. If we would relate these Cretaceous to Tertiary ages to the above reported highpressure metamorphic event, we would conclude that more than just an oceanic plateau collided with northwestern South America as it was proposed, for instance, by Reynaud et al (1999), Bosch et al (2002) and Hughes and Pilatasig (2002) for Cretaceous to Palaeogene times. Alternatively, the high-pressure metamorphism could be older and, thus, would lead to the potential discovery of a so far unknown continental fragment which had collided with northwestern South America.…”
Section: Inst F Mineralogie Und Kristallchemie Universität Stuttgamentioning
confidence: 84%